PENERAPAN STRATEGI REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI IPA SMA NEGERI 14 PEKANBARU - Utari Ramadhani S; R.Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : It has been applied the REACT strategy to improve students learning results on the subject of thermochemical in class XI IPA SMAN 14 Pekanbaru. The research is an experimental research with pretest-posttest design. The samples of this research were the students of class XI IPA3 as the experimental class and the students of class XI IPA1 as the control class. They were randomly determined after given the tests of normality and homogeneity. Experimental class is a class which was given a treatment by applying REACT strategy in learning process. The data were analyzed by using t-test. Based on the result of data analysis, it obtained tscore > ttable (5,38 > 1,67), it means that the application of REACT strategy can improve student learning results on the subject of thermochemical in class XI IPA SMAN 14 Pekanbaru. The improvement category of student achievement at experiment class was high category with normalized N-gain which is 0,76.Key Words : REACT strategy, Learning Results, Thermochemical